TRAIT PERSONALITY DALAM MENENTUKAN LEVEL KESEHATAN MENTAL ANAK AKIBAT DARI PEREMPUAN KEPALA KELUARGA: PERSPEKTIF PSIKOLOGI ISLAM - Rahmaddani, Vikri; Bahri Ghazali; Hasan Mukmin; Siti Badiah; Rini Setiawati (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Abstract. This study aims to determine the role of Da’i personality traits in mapping the level of mental health of orphans based on the perspective of the Qur’an. This study used a qualitative approach involving thirty-four orphans aged 12–18, comprising 55% girls and 45% boys. Data were collected by exploring children’s experiences during the first three years since losing their father. The results showed that the first year is the most difficult time mentally for children, especially related to anxiety, stress, and communication disorders. This condition is influenced by physical, emotional, and social factors, and the absence of the father’s role. In this situation, a Da’i with an empathetic, communicative, and spiritual personality must provide guidance and a sense of security. As mentioned in QS, the Qur’an emphasizes the importance of caring for weak children. An-Nisa: 9. In the second year, the children’s mental condition has not shown significant improvement. Peers become the main emotional support, while a Da’i acts as a spiritual companion who helps children understand the meaning of loss and deal with the pressures of life, especially in the context of underprivileged families. QS. Al-Hujurat: 10 underlines the importance of social support in building solidarity and mental strength. Entering the third year, the child’s mental condition is greatly influenced by the experiences of the previous two years. Children who receive emotional support and spiritual guidance from a Da’i are more stable and mentally strong. This study confirms the importance of Da’i’s personality, such as patience, wisdom, and compassion, in accompanying orphans so that they continue to grow healthily, confidently, and do not lose hope, as in line with the principles of QS. Ar-Ra’d: 11.